1955
DOI: 10.1103/physrev.99.843
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Photoproduction ofπ0Mesons in Helium and (γ, n) Reaction on Helium at High Energies

Abstract: 843 so that q i and, finally, 3 M z =(M/j)(M z ) nlJT . (32) the form described in Appendix I, with the quantum numbers describing the subshell suppressed. Since only diagonal terms of the expectation value of the moment operator survive, M 2 =EkM| 2 [(^M(l),M,i^M(l)) + (^-M (2 ) >M22^/ 2-M (2 ))]. (34) APPENDIX II Let an arbitrary number of nucleons in the nljr subshell couple to a state with angular momentum / and Using Eq. (10) and realizing that an arbitrary number of nucleons from the n'Vj'r 1 subshell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1955
1955
1970
1970

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Experiments on the photodisintegration of alpha particles have been performed by Benedict and Woodward, 19 Halpern et al 20 Fuller, 6 de Saussure and Osborne, 21 and Smith and Barton. 22 Benedict and Woodward measured the cross sections for the production of protons of energies from 45 to 120 Mev produced from He 4 by a bremsstrahlung beam, and have expressed their results in terms of differential cross sections.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on the photodisintegration of alpha particles have been performed by Benedict and Woodward, 19 Halpern et al 20 Fuller, 6 de Saussure and Osborne, 21 and Smith and Barton. 22 Benedict and Woodward measured the cross sections for the production of protons of energies from 45 to 120 Mev produced from He 4 by a bremsstrahlung beam, and have expressed their results in terms of differential cross sections.…”
Section: Experimental Datamentioning
confidence: 99%
“…Halpern et al 20 20 ; the solid triangles, Fuller 6 ; the open circles, Osborne et al 21 ; the solid squares, Woodward et al 19 ; and the solid circle, Smith et al 22 The curve is used for the numerical calculation of ©• & and outgoing neutrons, and analyzed their yield curve by the photon difference method. We have read their cross sections also from their curve of photoneutron cross section for He 4 , de Saussure and Osborne 21 have investigated the photodisintegration reaction 7+He 4 -> He 3 +?£ by measuring the energy and angular distribution of the He 3 recoil nuclei for photon energies between 40 and 120 Mev.…”
Section: Experimental Datamentioning
confidence: 99%
“…[1][2][3][4] Other authors have also observed the elastic photoproduction of ir° mesons in deuterium 5,6 and helium. 7,8 The group at the * This work has been supported in part by the joint program of the U. S. Atomic Energy Commission and the Office of Naval…”
Section: Introductionmentioning
confidence: 99%